2022
DOI: 10.1039/d1qo01588e
|View full text |Cite
|
Sign up to set email alerts
|

Bromine and oxygen redox species mediated highly selective electro-epoxidation of styrene

Abstract: The olefin epoxidation is an essential transformation and arouses great interest among the scientific community for the key role of epoxide in the chemical industry. Traditional methods suffer from harmful...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…S14, ESI †), which is supposedly due to formation of tight heterostructures in the trimetallic phosphide, which could also improve the electrocatalytic efficacy positively. [47][48][49][50][51][52][53][54][55][56]…”
Section: Characterization and Analysis Of Materialsmentioning
confidence: 99%
“…S14, ESI †), which is supposedly due to formation of tight heterostructures in the trimetallic phosphide, which could also improve the electrocatalytic efficacy positively. [47][48][49][50][51][52][53][54][55][56]…”
Section: Characterization and Analysis Of Materialsmentioning
confidence: 99%
“…In the literature, an α-Fe 2 O 3 photoanode and a dye-sensitized photoanode have been explored for light-driven alkene epoxidation in a PEC configuration, but yielded low conversion and selectivity. On the other hand, halide-mediated electrochemical (EC) alkene oxidation has shown satisfying selectivity and efficiency toward epoxides in both aqueous and non-aqueous media . Recently, chloride-mediated electrosynthesis of ethylene oxide and propylene oxides from ethylene and propylene at high current density has been realized in a flow cell .…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 4B, upon adding 1 mL of H 2 18O, ion peaks attributed to 18 O-labeled BzH (m/z = 107, 108) are detected (red line) and no 16 O-labeled BzH (m/z = 105, 106) is found, proving that H 2 O is the sole oxygen resource for the formation of BzH. The kinetic isotope effect of the electrooxidation was calculated using the H 2…”
mentioning
confidence: 94%
“…[17][18][19][20][21] For instance, Sargent et al 17 reported Cl À -mediated oxidation of ethylene to ethylene oxide with high selectivity, which achieved a current density of 1 A cm À2 and a faradaic efficiency of B70%. Qian et al 18 demonstrated that bromine and oxygen redox species promote the highly selective electro-epoxidation of ST. With this advance as an inspiration, the electrooxidation of ST to form BzH might be realized by utilizing a reaction mediated by reactive oxygen species (ROS). Recently, Jin et al 20 realized the epoxidation of olefin using water as an oxygen source and monodispersed manganese oxide nanoparticles as the catalyst at a given potential.…”
mentioning
confidence: 99%
See 1 more Smart Citation